Understanding Unworked Time in Spain - Pilar Rey del Castillo (CESifo GmbH, 2024)
This paper explores the evolution of non-working time in Spain over recent years by analysing the results of two surveys conducted by the National Statistics Institute: the Quarterly Survey on Labor Costs and the Labor Force Survey. Using time series models and intervention analysis, potential reasons for the discrepancies between the two surveys are identified and a procedure is proposed to "reconcile" their results. Furthermore, the most notable change found in the behavior of non-working hours has been an increase of around 2% from the second quarter of 2019 as a result of the entry into force of a legal reform that implemented the mandatory recording of working time.
Keywords: C22; C81; C83; J21; J22; 330; labor cost survey; labor force survey; time series; ARIMA models; intervention analysis